2014
DOI: 10.1039/c4ra07877b
|View full text |Cite
|
Sign up to set email alerts
|

Host–guest inclusion complexes of α and β-cyclodextrins with α-amino acids

Abstract: The innovative study reveals the formation of 1:1 hosts–guest inclusion complexes for all the titled α-amino acids in the hydrophobic cavity of both α and β-cyclodextrin. The thermodynamic parameters for inclusion were studied depending on size and state of the guest molecules to draw inferences about contributions to the overall binding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 12 publications
2
53
0
2
Order By: Relevance
“…[16][17] It is observed that γ for aqueous solution of IL show and also surrounded by water molecules. This is also in correlation with the data from density and viscosity measurements, discussing underway, undoubtedly establish that β-CD has the favourable structure for the formation of inclusion complexes with the above selected IL.…”
Section: Surface Tensionmentioning
confidence: 93%
“…[16][17] It is observed that γ for aqueous solution of IL show and also surrounded by water molecules. This is also in correlation with the data from density and viscosity measurements, discussing underway, undoubtedly establish that β-CD has the favourable structure for the formation of inclusion complexes with the above selected IL.…”
Section: Surface Tensionmentioning
confidence: 93%
“…Aromatic amino acids are reported to be the principal responsible of the interaction and the formation of the host-guest complexes (Loftsson and Brewster 1996). The aim of the present work is to complement the available literature data (Kahle and Holzgrabe 2004;Rekharsky and Inoue 1998;Roy et al 2014) by detailing the interaction of β-CD with different tripeptides designed in such a way that each of them contains a different aromatic amino acid in different position in the chain.…”
Section: Introductionmentioning
confidence: 94%
“…The plot also shows that there is a single discernible break in the curve, which not only points out the formation of IC but also indicates the 1:1 stoichiometric ratio for the IC formed ( Figure 7) [34,35]. The value of γ and corresponding concentrations of vitamin and β-CD at break have been listed in Table 1, which also indicate that at break point the concentration ratio of host and guest is about 1:1, establishing the formation of 1:1 IC between the studied vitamin and β-CD [8,36]. …”
Section: Surface Tension Study Elucidates the Inclusion As Well As Stmentioning
confidence: 97%
“…Formation of the host-guest IC is the dimensional suitability between the two species, which is favoured by the unique cyclodextrin molecule that provides an appropriate condition by encapsulating the apolar part of the guest molecule inside the cavity, as well as stabilizing the polar part by the polar rims [36]. The other driving force for the formation of IC is the release of the water molecules from the hydrophobic cavity into the bulk thereby increasing the entropy of the system [1,51].…”
Section: Isothermal Titration Calorimetry: Characterization Of the Comentioning
confidence: 99%